The Automobile Girls at Chicago; Or, Winning Out Against Heavy Odds - Crane, Laura Dent (Salt Lake City, UT : Project Gutenberg, 2010)
"The Automobile Girls at Chicago; Or, Winning Out Against Heavy Odds" by Laura Dent Crane is a fictional tale written in the early 20th century. The story centers around a group of adventurous young women, known as the 'Automobile Girls,' who embark on a trip to Chicago, facing various challenges and mysteries along the way. The novel suggests themes of friendship, bravery, and the spirit of adventure that resonate with the era's fascination with automobiles and modern travel. At the start of the narrative, we are introduced to Barbara and Mollie Thurston, who, during their train journey, overhear a tense conversation between two men that hints at a brewing financial conflict. Following a train accident that leaves them in a precarious situation, they are determined to find their friend, Grace Carter, who is unconscious from the incident. As the girls tackle the aftermath of the wreck and uncover further mysteries, including the identity of one of the men from the train, the seeds are sown for a thrilling adventure intertwined with elements of danger and excitement as they navigate their new surroundings in Chicago. (This is an automatically generated summary.)
Release date is 2010-05-19
E-text prepared by Suzanne Shell, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Friendship -- Juvenile fiction; Vacations -- Juvenile fiction; Treasure troves -- Juvenile fiction; Girls -- Societies and clubs -- Juvenile fiction; Mystery and detective stories; Automobile travel -- Juvenile fiction; Chicago (Ill.) -- Juvenile fiction